Avicides - Frederick M. Fishel (EDIS)
By and large, birds are beneficial because they provide enjoyment and recreation to humans and are vital to ecosystem balance. However, occasionally some species can compete with human interests. When these situations occur, some forms of control may become necessary. Avicides are pesticides designed to kill or repel pest birds. This new 2-page document addresses those avicides currently registered for use in Florida. Written by Frederick M. Fishel and published by the UF/IFAS Pesticide Information Office. https://edis.ifas.ufl.edu/pi281